Intergenerational living and learning: The value and risks of co‐locating retirement villages on secondary school campuses – Evaluating the GrandSchools vision. (4th July 2022) - Trotter, Mark; Sanders, Paul; Lindquist, Marissa; Miller, Evonne; Hajirasouli, Aso; Blake, Andrea; Harrington, Rosamund; Olsen, Heidi; Tyvimaa, Tanja; Pepping, Gert‐Jan; Kuys, Suzanne; Drogemuller, Robin
Abstract: Objectives: GrandSchools is a new concept which co‐locates retirement villages with secondary schools in one physical environment. Designed to enhance the health and well‐being of both younger and older generations, this intergenerational‐shared campus model promotes intergenerational inclusivity and active learning and living. In this paper, we explore stakeholder experts' perceptions of current opportunities and impediments to this proposed intergenerational learning and living model. Methods: A qualitative study reporting on findings from an industry seminar ( n = 50) and key interviews ( n = 10) from stakeholders in education, health, higher education, the management and operation of retirement villages, and design firms. Results: Three key themes summarised participants' assessment of the value, risks and what needs to change in order for intergenerational living and learning to become a reality. Conclusions: By bringing younger and older generations together in one shared campus location, GrandSchools is a novel idea to promote intergenerational inclusivity, enhancing the health and well‐being of our whole community.